Razvoj koncepta funkcijske zvrstnosti v slovenskem jezikoslovju - Dukič, Davorin (Slavistična revija, 2010)
The article discusses the realtionship of Slovene linguistics with the conceptof register variation, traditionally called funkdijska zvrstnost. to identify the key features of the development of the theoretical concepts, the author analyzes linguistic studies by numerous authors, which are, considering the time of their compilation, considered classical theories of register variation, chronologically divided into three periods. At the end of the survey, the author presents the findings related to the interpretations of register variation, the development of the appropriate terminological apparatus, and the classification of registers.
Keywords: funkcijska lingvistika; jezikoslovje; knjižni jezik; linguistics; Slovene; slovenščina; standard language